2014
DOI: 10.1080/19407963.2013.877471
|View full text |Cite
|
Sign up to set email alerts
|

The search for meaningful tourism indicators: the case of the International Upper Great Lakes Study

Abstract: The recent rise in evidence-based policy-making means tourism interests are increasingly impacted by policies informed by quantifiable data. With complex issues impacting stakeholders with differing and often competing interests, policy-makers sometimes commission large interdisciplinary studies to help synthesize the potential data that can be used to inform the policy-making process. To help manage the data generated by these studies, study leaders often set guidelines for the types of data that can be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…While McLoughlin and Hanrahan's (2019) longitudinal study on tourism planning in Ireland found a slight shift towards Local Authorities embracing greater levels of sustainability, the scarcity of on-going research and the measuring and monitoring of a range of tourism impacts by Irelands Local Authorities not only appears to refute what Head (2008) identifies as the essence of the design and implementation of programmes but also against the recommendations of the European Commission [EC] (2016) which continue to emphasise the important of collecting data on a broad range of issues relevant to tourism to help build an accurate picture of tourist activity at local level. Therefore, it would be necessary to discuss the reasons behind this lack of evidence-informed planning for tourism in Ireland. Despite what has been considered previously by McCole and Joppe (2014), it is clear from this study is that the vast majority of Local Authorities in Ireland do not benefit from or gathering quality data on tourism activity. The absence of sufficient data has been raised previously by Scott and Becken (2010) when they discussed how the lack of information on climate change, carbon footprint and waste management can impede upon the progress towards greater sustainability in tourism.…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…While McLoughlin and Hanrahan's (2019) longitudinal study on tourism planning in Ireland found a slight shift towards Local Authorities embracing greater levels of sustainability, the scarcity of on-going research and the measuring and monitoring of a range of tourism impacts by Irelands Local Authorities not only appears to refute what Head (2008) identifies as the essence of the design and implementation of programmes but also against the recommendations of the European Commission [EC] (2016) which continue to emphasise the important of collecting data on a broad range of issues relevant to tourism to help build an accurate picture of tourist activity at local level. Therefore, it would be necessary to discuss the reasons behind this lack of evidence-informed planning for tourism in Ireland. Despite what has been considered previously by McCole and Joppe (2014), it is clear from this study is that the vast majority of Local Authorities in Ireland do not benefit from or gathering quality data on tourism activity. The absence of sufficient data has been raised previously by Scott and Becken (2010) when they discussed how the lack of information on climate change, carbon footprint and waste management can impede upon the progress towards greater sustainability in tourism.…”
Section: Resultscontrasting
confidence: 68%
“…Evidence-informed planning for tourism Head (2008) discussed how evidence has become central to the design, implementation and evaluation of policies and programmes. From a tourism perspective McCole and Joppe (2014) argue that gathering data on tourist activity is important for not only its future sustainability, but also how the destination is managed. Taking the connection between Local Authorities and tourism planning, recent studies have argued that the absence of data on tourism activity deprives Local Authorities of the opportunity to get ahead of challenges that tourism may present (Maguire & McLoughlin, 2019;McLoughlin et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Evidence-informed planning for tourism Head (2008) discussed how evidence has become central to the design, implementation and evaluation of policies and programmes. From a tourism perspective McCole and Joppe (2014) argue that gathering data on tourist activity is important for not only its future sustainability, but also how the destination is managed. Taking the connection between Local Authorities and tourism planning, recent studies have argued that the absence of data on tourism activity deprives Local Authorities of the opportunity to get ahead of challenges that tourism may present (Maguire & McLoughlin, 2019;McLoughlin et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%